(untitled) (International journal of medical sciences, 2026)
The use of antibiotics in the treatment of bacterial acute intestinal infections (AII) is a double-edged sword, often leading to the disruption of the gut microbiota and the development of antibiotic-associated dysbiosis (AAD). This article presents a randomized controlled trial conducted at the Department of Infectious Diseases of Andijan State Medical Institute. Using the IMRAD framework, the research evaluates the efficacy of a synbiotic regimen initiated simultaneously with antibiotic therapy versus standard care in preventing AAD in 150 pediatric patients. The study analyzes clinical outcomes, including diarrhea duration, and microbiological shifts in the colonic flora. The results demonstrate that the prophylactic use of multi-strain synbiotics significantly reduces the incidence of AAD, preserves the population of obligate anaerobes, and accelerates the restoration of intestinal homeostasis. The study concludes that "microbiome-protective" therapy should be an integral part of the protocol for managing acute intestinal infections.